Design and Implementation of a cryptographic system for images using Random number generator (Journal of the College of Basic Education, 2022)
In the present work the design and development of ciphering method on colored images is studied. The method use incryption keys for ciphering and deciphering, where a random number generation program is used to produce a set of values that determine the incryption keys. In that mid point circles generating algorithmis used to locate a number of interrelated circles so as to determine the pixels to be ciphered.